Photoinitiated hydrothiolation of pyranoid exo-glycals: the d-galacto and d-xylo cases. (2nd September 2015) - József, János; Juhász, László; Illyés, Tünde Zita; Csávás, Magdolna; Borbás, Anikó; Somsák, László
Abstract: Radical-mediated addition reactions of thiols to O -peracetylated exo -galactal and exo -xylal with 2, 2-dimethoxy-2-phenylacetophenone as the photoinitiator resulted in high yielding formation of the corresponding β-d -glycopyranosylmethyl-sulfide derivatives (2, 6-anhydro-1-deoxy-1- S -substituted-1-thio-alditols) with exclusive regio- and very high stereoselectivity, including disaccharide mimicks with Gly-CH2 -S-Gly scaffolds. Graphical abstract: Highlights: Photoinitiated thiol-ene reaction of O -peracetylated exo -glycals. Synthesis of β-d -glycopyranosylmethyl-sulfide type glycomimetics. Exclusive regio- and stereoselectivity with exo -galactal. Exclusive regio- and very high stereoselectivity with exo -xylal. Disaccharide mimicks of Gly-CH2 -S-Gly scaffolds.